Medical-legal, legislative and ethical aspects of occupational hearing loss - Rosignoli, Mauro; Galli, Jacopo; D'Alatri, Lucia (Medicina e Morale, 1990)
The authors outline some clinical aspects of occupational hearing loss, and report on the Italian laws and evaluation criteria of this damage, to the hearing and including some considerations about the social, ethical and occupational implications. They also emphasize the present deficiencies of the law, the variety of the methods aimed at the quantification of the biological damage, the problems concerning simulation, and the difficulties in distinguishing between occupational hearing loss and presbycusis. The authors finally suggest further study of the quantification of hyndemnizable hearing loss, the methodologies concerning the evaluation of the damage and the professional categories involved, in order to contribute to the resolution of residual controversies about occupational hearing loss.